Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

If x and y are integers and 4xy = x^2*y+4y, what is the value of xy?

(1) y-x = 2 (2) x^3 <0

what I did : 4xy = x^2y+4y 4x = x^2+4 x^2-4x+4 = 0 (x-2)^2=0 x = 2 is this wrong?

You cannot divide 4xy=x^2y+4y by y and write 4x=x^2+4, because y can be zero and division be zero is not allowed. Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero. So when you divide by y you assume, with no ground for it, that y does not equal to zero thus exclude a possible solution.

If x and y are integers and 4xy = x^2*y+4y, what is the value of xy?

\(4xy=x^2*y+4y\) --> \(x^2*y-4xy+4y=0\) --> \(y(x^2-4x+4)=0\) --> \(y(x-2)^2=0\) --> either \(x=2\) or \(y=0\) (or both).

(1) y-x = 2 --> if \(x=2\) then \(y=4\) and \(xy=8\) but if \(y=0\) then \(x=-2\) and \(xy = 0\). Not sufficient.

(2) x^3<0 --> \(x<0\), so \(x\neq{2}\) which means that \(y\) must equal to zero --> \(xy=0\). Sufficient.

Re: If x and y are integers and 4xy = x^2*y+4y, what is the [#permalink]

Show Tags

25 May 2012, 19:15

thanks bunuel. Its a common error to 'cancel' y on both sides. I fell prey to the same mistake. However, just to clarify, basically when x = 2 then y can take any value and when y=0 x can take any value. In either case xy=0?

thanks bunuel. Its a common error to 'cancel' y on both sides. I fell prey to the same mistake. However, just to clarify, basically when x = 2 then y can take any value and when y=0 x can take any value. In either case xy=0?

If y=0 then x can take any value - TRUE. In this case xy=0. If x=2 then y can take any value - TRUE. In this case xy=0 only if y=0 but for any other possible value of y xy does not equal to zero (for example consider x=2 and y=1).

Re: If x and y are integers and 4xy = x^2*y+4y, what is the [#permalink]

Show Tags

26 May 2012, 07:09

Bunuel wrote:

If x=2 then y can take any value - TRUE. In this case xy=0 only if y=0 but for any other possible value of y xy does not equal to zero (for example consider x=2 and y=1).

Just by looking at this equation y(x^2 -4x+4) = 0 either the quadratic term has to equal 0, in which case x=2, or y has to equal to zero. In which scenario will y =1 and x=2 occur?

If x=2 then y can take any value - TRUE. In this case xy=0 only if y=0 but for any other possible value of y xy does not equal to zero (for example consider x=2 and y=1).

Just by looking at this equation y(x^2 -4x+4) = 0 either the quadratic term has to equal 0, in which case x=2, or y has to equal to zero. In which scenario will y =1 and x=2 occur?

Again: \(y(x-2)^2=0\) means that either \(x=2\) or \(y=0\) (or both).

Now, if \(x=2\) then \(y\) can take ANY value including 1.

Re: If x and y are integers and 4xy = x^2*y+4y, what is the [#permalink]

Show Tags

14 Sep 2013, 03:21

Bunuel wrote:

kashishh wrote:

If x and y are integers and 4xy = x^2*y+4y, what is the value of xy?

(1) y-x = 2 (2) x^3 <0

what I did : 4xy = x^2y+4y 4x = x^2+4 x^2-4x+4 = 0 (x-2)^2=0 x = 2 is this wrong?

You cannot divide 4xy=x^2y+4y by y and write 4x=x^2+4, because y can be zero and division be zero is not allowed. Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero. So when you divide by y you assume, with no ground for it, that y does not equal to zero thus exclude a possible solution.

If x and y are integers and 4xy = x^2*y+4y, what is the value of xy?

\(4xy=x^2*y+4y\) --> \(x^2*y-4xy+4y=0\) --> \(y(x^2-4x+4)=0\) --> \(y(x-2)^2=0\) --> either \(x=2\) or \(y=0\) (or both).

(1) y-x = 2 --> if \(x=2\) then \(y=4\) and \(xy=8\) but if \(y=0\) then \(x=-2\) and \(xy = 0\). Not sufficient.

(2) x^3<0 --> \(x<0\), so \(x\neq{2}\) which means that \(y\) must equal to zero --> \(xy=0\). Sufficient.

Answer: B.

Hope it's clear.

instead of taking LHS to RHS , I brought RHS to LHS and got 4xy-x^2y - 4y = 0 now y (4x-x^2- 4 )= 0 y (-x^2 +4x - 4)= 0 y (x+2)^2= 0 either y = 0 or x = -2 now obviously x=-2 does not satisfy 4xy = x^2*y+4y, now I was expecting the same answer both ways. Now am I doing something wrong,or is it just one of those cases where the equation works a certain way and not the other way

by the way factorization of -x^2 +4x-4 =0 is (x+2)^2 right? if x^2 has a coefficient we have to multiply the constant (-4) with the coefficient of x^2 do we not. _________________

If x and y are integers and 4xy = x^2*y+4y, what is the value of xy?

(1) y-x = 2 (2) x^3 <0

what I did : 4xy = x^2y+4y 4x = x^2+4 x^2-4x+4 = 0 (x-2)^2=0 x = 2 is this wrong?

You cannot divide 4xy=x^2y+4y by y and write 4x=x^2+4, because y can be zero and division be zero is not allowed. Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero. So when you divide by y you assume, with no ground for it, that y does not equal to zero thus exclude a possible solution.

If x and y are integers and 4xy = x^2*y+4y, what is the value of xy?

\(4xy=x^2*y+4y\) --> \(x^2*y-4xy+4y=0\) --> \(y(x^2-4x+4)=0\) --> \(y(x-2)^2=0\) --> either \(x=2\) or \(y=0\) (or both).

(1) y-x = 2 --> if \(x=2\) then \(y=4\) and \(xy=8\) but if \(y=0\) then \(x=-2\) and \(xy = 0\). Not sufficient.

(2) x^3<0 --> \(x<0\), so \(x\neq{2}\) which means that \(y\) must equal to zero --> \(xy=0\). Sufficient.

Answer: B.

Hope it's clear.

instead of taking LHS to RHS , I brought RHS to LHS and got 4xy-x^2y - 4y = 0 now y (4x-x^2- 4 )= 0 y (-x^2 +4x - 4)= 0 y (x+2)^2= 0 either y = 0 or x = -2 now obviously x=-2 does not satisfy 4xy = x^2*y+4y, now I was expecting the same answer both ways. Now am I doing something wrong,or is it just one of those cases where the equation works a certain way and not the other way

by the way factorization of -x^2 +4x-4 =0 is (x+2)^2 right? if x^2 has a coefficient we have to multiply the constant (-4) with the coefficient of x^2 do we not.

You could expand \((x+2)^2\) to check your reasoning: \((x+2)^2=x^2+2x+4\), while \(-x^2 +4x-4=-(x^2-4x+4)=-(x-2)^2\). Thus, \(y(4x-x^2- 4 )=0\) can be written as \(-y(x-2)^2=0\) --> \(x=2\) or \(y=0\).

Re: If x and y are integers and 4xy = x^2*y+4y, what is the [#permalink]

Show Tags

14 Sep 2013, 03:59

1

This post received KUDOS

Bunuel wrote:

stne wrote:

instead of taking LHS to RHS , I brought RHS to LHS and got 4xy-x^2y - 4y = 0 now y (4x-x^2- 4 )= 0 y (-x^2 +4x - 4)= 0 y (x+2)^2= 0 either y = 0 or x = -2 now obviously x=-2 does not satisfy 4xy = x^2*y+4y, now I was expecting the same answer both ways. Now am I doing something wrong,or is it just one of those cases where the equation works a certain way and not the other way

by the way factorization of -x^2 +4x-4 =0 is (x+2)^2 right? if x^2 has a coefficient we have to multiply the constant (-4) with the coefficient of x^2 do we not.

You could expand \((x+2)^2\) to check your reasoning: \((x+2)^2=x^2+2x+4\), while \(-x^2 +4x-4=-(x^2-4x+4)=-(x-2)^2\). Thus, \(y(4x-x^2- 4 )=0\) can be written as \(-y(x-2)^2=0\) --> \(x=2\) or \(y=0\).

Hope it's clear.

I think I am still missing something, can you please show me how to factorize -x^2+4x-4= 0 without taking out the negative sign, answer should be same right? Thank you _________________

- Stne

Last edited by stne on 14 Sep 2013, 04:07, edited 1 time in total.

instead of taking LHS to RHS , I brought RHS to LHS and got 4xy-x^2y - 4y = 0 now y (4x-x^2- 4 )= 0 y (-x^2 +4x - 4)= 0 y (x+2)^2= 0 either y = 0 or x = -2 now obviously x=-2 does not satisfy 4xy = x^2*y+4y, now I was expecting the same answer both ways. Now am I doing something wrong,or is it just one of those cases where the equation works a certain way and not the other way

by the way factorization of -x^2 +4x-4 =0 is (x+2)^2 right? if x^2 has a coefficient we have to multiply the constant (-4) with the coefficient of x^2 do we not.

You could expand \((x+2)^2\) to check your reasoning: \((x+2)^2=x^2+2x+4\), while \(-x^2 +4x-4=-(x^2-4x+4)=-(x-2)^2\). Thus, \(y(4x-x^2- 4 )=0\) can be written as \(-y(x-2)^2=0\) --> \(x=2\) or \(y=0\).

Hope it's clear.

I think I am still missing something, can you please show me how to factorize -x^2+4x-4= 0 without taking out the negative sign, answer should be same right? Thank you

You can factor -x^2 + 4x - 4 only as -(x-2)^2. _________________

Re: If x and y are integers and 4xy = x^2*y+4y, what is the [#permalink]

Show Tags

14 Sep 2013, 05:40

1

This post received KUDOS

Bunuel wrote:

stne wrote:

Bunuel wrote:

You could expand \((x+2)^2\) to check your reasoning: \((x+2)^2=x^2+2x+4\), while \(-x^2 +4x-4=-(x^2-4x+4)=-(x-2)^2\). Thus, \(y(4x-x^2- 4 )=0\) can be written as \(-y(x-2)^2=0\) --> \(x=2\) or \(y=0\).

Hope it's clear.

I think I am still missing something, can you please show me how to factorize -x^2+4x-4= 0 without taking out the negative sign, answer should be same right? Thank you

You can factor -x^2 + 4x - 4 only as -(x-2)^2.

Thank you +1, I was under the impression that it was possible to factor -x^2 +4x-4 as it is and it was not necessary to take out the negative sign. One of those mistakes , waiting to happen. _________________

Re: If x and y are integers and 4xy = x^2*y+4y, what is the [#permalink]

Show Tags

03 Jan 2014, 12:14

Hi Bunuel, Thanks for the wonderful response. Please let me know that we should you use it as truth statement for DS question (Algebra) that "Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero". I surely follow it that reduce variable in algebra only when I am sure that they are not equal to 0.

Please do explain one doubt .What you said make logical sense but it contradicts from my previous knowledge that if we have an equation and two expression are equal to each other than we can reduce the common variable such as y from both side and there is no where mention that variable not equal to 0.

Hi Bunuel, Thanks for the wonderful response. Please let me know that we should you use it as truth statement for DS question (Algebra) that "Never reduce equation by variable (or expression with variable), if you are not certain that variable (or expression with variable) doesn't equal to zero. We can not divide by zero". I surely follow it that reduce variable in algebra only when I am sure that they are not equal to 0.

Please do explain one doubt .What you said make logical sense but it contradicts from my previous knowledge that if we have an equation and two expression are equal to each other than we can reduce the common variable such as y from both side and there is no where mention that variable not equal to 0.

Yes, the property is true.

Consider simple example: xy=x. If you reduce this expression by x you get definite answer that y=1 but if there x=0, then y is not necessary to be 1, it can be any number.

Correct solution would be xy=x --> x(y-1)=0 --> x=0 OR y=1.

This is the kickoff for my 2016-2017 application season. After a summer of introspect and debate I have decided to relaunch my b-school application journey. Why would anyone want...

Check out this awesome article about Anderson on Poets Quants, http://poetsandquants.com/2015/01/02/uclas-anderson-school-morphs-into-a-friendly-tech-hub/ . Anderson is a great place! Sorry for the lack of updates recently. I...

Time is a weird concept. It can stretch for seemingly forever (like when you are watching the “Time to destination” clock mid-flight) and it can compress and...